2012
DOI: 10.1188/12.onf.e380-e389
|View full text |Cite
|
Sign up to set email alerts
|

Changes and Predictors of Unmet Supportive Care Needs in Taiwanese Women With Newly Diagnosed Breast Cancer

Abstract: Oncology nurses should assess the needs of patients with breast cancer and provide them with individualized, culturally sensitive informational, social, and emotional support from breast cancer diagnosis through the first four months of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
48
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 33 publications
(53 reference statements)
10
48
1
3
Order By: Relevance
“…The women in this study had high unmet supportive care needs, with unmet needs greatest in the health system and information, and physical and daily living domains. This is similar to Asian studies conducted in Taiwan (Liao et al, 2012), Japan (Nakaguchi et al, 2013) and Hong Kong Li et al, 2013) wherein breast cancer patients reported high rates of unmet supportive care needs, particularly in the informational domain. This contrasts with research conducted in Western countries, including Switzerland (Schmid-Büchi et al, 2012), Australia (Hodgkinson et al, 2007;McDowell et al, 2010), Germany (Lam et al, 2011), England (Armes et al, 2009;Harrison et al, 2011) and Canada (Whelan et al, 1997), wherein breast cancer patients have moderate levels of supportive care needs and unmet needs were highest in the psychological domain.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The women in this study had high unmet supportive care needs, with unmet needs greatest in the health system and information, and physical and daily living domains. This is similar to Asian studies conducted in Taiwan (Liao et al, 2012), Japan (Nakaguchi et al, 2013) and Hong Kong Li et al, 2013) wherein breast cancer patients reported high rates of unmet supportive care needs, particularly in the informational domain. This contrasts with research conducted in Western countries, including Switzerland (Schmid-Büchi et al, 2012), Australia (Hodgkinson et al, 2007;McDowell et al, 2010), Germany (Lam et al, 2011), England (Armes et al, 2009;Harrison et al, 2011) and Canada (Whelan et al, 1997), wherein breast cancer patients have moderate levels of supportive care needs and unmet needs were highest in the psychological domain.…”
Section: Discussionsupporting
confidence: 69%
“…Investigations of supportive care needs among South East Asian breast cancer patients suggests that a large percentage have unmet needs Liao et al, 2012;Au et al, 2013;Li et al, 2013;Nakaguchi et al, 2013). Previous Iranian researchers have documented high rates of disrupted psychological functioning among breast cancer patients (Montazeri et al, 2002;Tavoli et al, 2008), and a lack of disease and treatment related information or education (Montazeri et al, 2002), but evidence of unmet supportive care needs is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a systematic literature review on unmet needs of newly diagnosed older cancer patients undergoing active cancer treatment revealed that the level of unmet needs after the start of treatment is high with the most common needs being psychological and information needs (Puts et al, 2012). Several longitudinal studies have demonstrated that unmet supportive care needs decrease over time yet may persist over months or years, and that individual patient needs change during treatment and later phases of survivorship (Armes et al, 2009;Liao et al, 2012;McDowell et al, 2010;Minstrell et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…The mean score of depression in this study was lower than that of patients undergoing treatment in a survey by Chen et al (2012), and higher than patients who had completed treatment. Such findings may reflect that active treatment is a possible stress event.…”
Section: Discussionmentioning
confidence: 45%
“…SSS-m items are scored from 0 (not at all) to 3 (always), with higher total scores indicating higher levels of social support. The scale has been reported to have satisfactory psychometric properties in previous study in Taiwanese (Liao et al, 2012).…”
Section: Questionnairementioning
confidence: 99%